Evidence Based Treatment of Alopecia Areata - Eva Hariani; Nelva K. Jusuf (Berkala Ilmu Kesehatan Kulit dan Kelamin, 2017)
Background: Alopecia areata is a chronic autoimmune disease, involving non-scarring hair loss, which affects hair follicles and sometimes nails. Hair loss pattern presents as patchy alopecia, ophiasis, ophiasis inversa (sisapho), reticularis or diffuse. Alopecia areata is common disorder and can impact on patient’s quality of life. Purpose: To review commonly used evidence based treatments of alopecia areata. Review: A number of treatments for alopecia areata have been showed to stimulate hair growth but there is no universally proven therapy that sustains remission. There is high rate of spontaneous remission in alopecia areata makes difficult to assess effectiveness of treatment (spontaneous remission occurs in up to 80% of patients). Numerous of topical and systemic treatment for alopecia areata have been assessed by randomized controlled trials. However management of patients with alopecia areata is still challenging. Conclusion: A number of treatments were found to be effective for alopecia areata. Based on randomized controlled trials, contact immunotherapy has the highest therapeutic evidence based level. Potent topical corticosteroid and intralessional corticosteroids are recommended for limited patchy hair loss and contact immunotherapy for extensive patchy hair loss and alopecia areata totalis/universalis.